2012
DOI: 10.2174/138920312804142129
|View full text |Cite
|
Sign up to set email alerts
|

Osmotin, a Pathogenesis-Related Protein

Abstract: Plants protect themselves from pathogen invasion through the local expression of a variety of pathogenesis-related proteins. They are highly diverse in both primary structure and length, and exhibit different direct antimicrobial activity. This text reviews the knowledge of osmotin, antimicrobial protein involved in innate immunity of plants. Osmotin belongs to the fifth class of the group of pathogenesis-related (PR) proteins and has been found in different plants species, in every case osmotin is cysteine-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…It is generally accepted that the plasma membrane contains proteins that are fundamental for stress‐signal perception and transduction of stress signals into downstream cellular responses. Previous studies have shown that plant osmotin and OLPs are likely to be situated within a signal transduction pathway of stress response (Abdin et al , Husaini and Rafiqi , Viktorova et al ). Our results on the plasma membrane localization and early activation of mRNA in stress response of TlOsm strongly support its function in stress signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that the plasma membrane contains proteins that are fundamental for stress‐signal perception and transduction of stress signals into downstream cellular responses. Previous studies have shown that plant osmotin and OLPs are likely to be situated within a signal transduction pathway of stress response (Abdin et al , Husaini and Rafiqi , Viktorova et al ). Our results on the plasma membrane localization and early activation of mRNA in stress response of TlOsm strongly support its function in stress signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among the potential stress‐responsive candidate genes identified from the highly drought‐tolerant plant T . loliiformis , the osmotin gene ( TlOsm ) represents one of the most potent candidates for improving crop tolerance to abiotic stresses through genetic engineering due to increasing evidence supporting the role of osmotin as key regulators in response to abiotic stresses (Husaini and Rafiqi , Viktorova et al , Kumar et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, the protease inhibitor, miraculin-like protein 2, which contains a thaumatin motif and has antifungal activity (Tsukuda et al , 2006), was highly expressed at the protein level (Supplementary Table S6, spot a26). It is worth noting that miraculin-like protein and osmotin 34 (Supplementary Table S6, spot 1) were involved in plant tolerance to pathogen infections and resistance to water deficiency (Gimeno et al , 2009; Viktorova et al , 2012). HSPs play important roles in the re-establishment of cellular homeostasis by partially binding to the denatured proteins and preventing irreversible protein inactivation and aggregation under raised heat conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic adjustment is a key phenomenon for maintaining water balance and cell turgor during osmotic stress and thus contributes to enhanced photosynthetic efficiency and growth (Das and Chakraborty 2016). Osmotins impart osmo-tolerance to plants possibly through ion sequestration or conferring protection through some structural or metabolic alterations at the cellular and molecular level (Viktorova et al 2012). Along with OLPs (Osmotin-like proteins), they negotiate abiotic stress responses in plants and their increased expression is mostly determined by drought (Atkinson and Urwin 2012), desiccation, or chilling/freezing stress (Aslam et al 2009).…”
Section: Osmotinsmentioning
confidence: 99%